2015
DOI: 10.1016/j.jcv.2014.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Successful recovery of MERS CoV pneumonia in a patient with acquired immunodeficiency syndrome: A case report

Abstract: Middle East Respiratory Syndrome Coronavirus (MERS CoV) may cause severe pneumonia with significant morbidity and mortality, particularly in patients with multiple comorbid condition. MERS CoV pneumonia has not been previously reported in patients with Human Immunodeficiency Virus (HIV). Herein, we report a case of MERS CoV pneumonia with a successful outcome in a patient recently diagnosed with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 11 publications
(13 reference statements)
4
30
0
Order By: Relevance
“…A total of 1095 references were retrieved. Upon screening them regarding inclusion and exclusion criteria from Section 2, eleven references were included for data extraction and analysis . Additionally, 5 references were identified through manual search .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1095 references were retrieved. Upon screening them regarding inclusion and exclusion criteria from Section 2, eleven references were included for data extraction and analysis . Additionally, 5 references were identified through manual search .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 16 studies including 116 patients, 10 were case reports, 2 were case series, and 4 were observational studies . Saudi Arabia was the country of origin for patients in 13 studies, and the rest were from France, Greece, and Qatar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical course is more severe in immunocompromised patients (6), (although recent case reports indicate that some recover) (45,46), and in pregnant women, where infection has been shown to result in stillbirths. The clinical course is more likely to be mild in individuals without underlying medical conditions (7,(47)(48)(49).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…As per the authors’ knowledge, two studies have so far addressed clinical improvement on laboratory‐confirmed MERS‐CoV patients . The first study, Shalhoub et al, was based on a case report in which their observations may not be generalized to a wider MERS‐CoV population. The second study, Al‐Turaiki et al, utilized publicly available data from the Saudi Ministry of Health.…”
Section: Introductionmentioning
confidence: 99%